Meckel′s diverticulum strangulated in an umbilical hernia - Komlatse Akakpo-Numado; Komla Gnassingbe; Komla Attipou; Azanledji Boume; Abossisso Sakiye; Hubert Tekou (Wolters Kluwer Medknow Publications, 2009)
Background: Strangulated Meckel′s diverticulum (MD) in an umbilical hernia (UH) is a rare event. We present herein a case of strangulated MD in UH in a child. Case Report: An 18-month girl was admitted with clinical features suggesting upper intestinal strangulation since seven days. Many attempts of reduction were done before admission. She was resuscitated and had exploratory laparotomy, which revealed the hernia sac containing a completely gangrenous MD. She had bowel resection and had an uneventful postoperative period. Conclusion: An MD may be the content of a strangulated UH. Bowel resection of the segment bearing the diverticulum is advisable if the latter is gangrenous.